2005
DOI: 10.1523/jneurosci.3610-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Functions of Cysteine-String Protein Analyzed atDrosophilaNerve Terminals

Abstract: The synaptic vesicle-associated cysteine-string protein (CSP) is important for synaptic transmission. Previous studies revealed multiple defects at neuromuscular junctions (NMJs) of csp null-mutant Drosophila, but whether these defects are independent of each other or mechanistically linked through J domain mediated-interactions with heat-shock cognate protein 70 (Hsc70) has not been established. To resolve this issue, we genetically dissected the individual functions of CSP by an in vivo structure/function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 48 publications
(95 reference statements)
5
49
0
Order By: Relevance
“…These loss-of-function white-eyed mutants lack filled pigment granules in the eye but were thought otherwise to be normal. Our subsequent (Bronk et al, 2005), western blot (Zinsmaier et al, 1990) DCSP, Drosophila cysteine string protein; KLH, keyhole limpet hemocyanin; BSA, bovine serum albumin; PFA, paraformaldehyde. white, brown and scarlet have reduced brain biogenic amines findings clearly revealed that white is not normal, however, either for histamine or other biogenic amines.…”
Section: Resultsmentioning
confidence: 99%
“…These loss-of-function white-eyed mutants lack filled pigment granules in the eye but were thought otherwise to be normal. Our subsequent (Bronk et al, 2005), western blot (Zinsmaier et al, 1990) DCSP, Drosophila cysteine string protein; KLH, keyhole limpet hemocyanin; BSA, bovine serum albumin; PFA, paraformaldehyde. white, brown and scarlet have reduced brain biogenic amines findings clearly revealed that white is not normal, however, either for histamine or other biogenic amines.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the CSP family are involved in exocytosis, and they bind to secretory vesicle membranes (e.g., synaptic vesicles, chromaffin granules, zymogen granules) via their hydrophobic side chains of palmitoyl (6,7,38). CSP was first discovered in retina and brain of Drosophila as a neuronal-specific protein (39) and, since then, wide expression of several CSP isoforms has been shown in both neuronal and nonneuronal tissues. Airway and mammary epithelial cells have been reported previously to express CSP (9, 21).…”
Section: Discussionmentioning
confidence: 99%
“…The value for the dissociation constant (K d ) was taken as 865 nM following previous work by Macleod et al (2002) and Bronk et al (2005). Briefly, the maximum (R max ) and minimum (R min ) fluorescence values for the preparation in the experimental chamber are obtained and used to calculate the K d of the indicator (Grynkiewicz et al 1985).…”
Section: Methodsmentioning
confidence: 99%